HEALTH CONDITION OF ELDERLY ENROLLED IN FAMILY HEALTH STRATEGY OF NUMBER 10 THE CITY OF ITAJAÍ-SC (Fiep Bulletin - online, 2013)
With increased life expectancy and longevity, the concern with functional capacity and health status of the elderly becomes relevant. Functional capacity is characterized by independence and ability to perform certain activities. Given that the goal of this research is to assess the health status of the elderly multidimensional city of Itajai, Santa Catarina, considering the functional capacity and associated morbidity and self-perceived health in the elderly. This is a population-based descriptive and quantitative character. The target population is the elderly aged over 60 years of both sexes, who agreed to participate in the study, enrolled in Family Health Strategy No. 10 of the Basic Health Unit of Don Bosco neighborhood in Itajai, SC. As an instrument used was a questionnaire Brazil Old Age Schedule (BOAS). Of the 101 seniors, 95% are satisfied with their life in general and 78.2% reported good health / good. Among the major health problems such stands out Hypertension, Diabetes Mellitus and Arthritis. In relation to functional capacity, the elderly showed high levels of functionality and autonomy, despite high prevalence of morbidity. This proves that the best health conditions are related to functional capacity and not with the presence of disease. We conclude that the population in general regard their health as good \ great, with low levels of high prevalence of disability and morbidity. Hence arises the need for maintenance actions and prevention of functional capacity, encouraging active living and healthy aging.
Keywords: Functional capacity; elderly; disability and health; physiotherapy